2022
DOI: 10.3390/curroncol29090474
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms Based on Serum N-glycome for Diagnosis of Papillary Thyroid Microcarcinoma and Prediction of Lymph Node Metastasis

Abstract: Non-invasive biomarkers for the diagnosis and prognosis of papillary thyroid microcarcinoma (PTMC) are still urgently needed. We aimed to characterize the N-glycome of PTMC, and establish nomograms for the diagnosis of PTMC and the prediction of lymph node metastasis (LNM). N-glycome of PTMC (LNM vs. non-LNM, capsular invasion (CI) vs. non-CI (NCI)) and matched healthy controls (HC) were quantitatively analyzed based on mass spectrometry. N-glycan traits associated with PTMC/LNM were used to create binomial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The discriminative power, calibration, and clinical utility of our nomogram in predicting LNM in PTMC were found to be high in both the training and validation sets. Additionally, when compared to other predictive models and nomograms, such as the BRAF V600E mutation model, 14 the sonographic features scoring system, and Liu's nomogram, 19 our tool demonstrated superior accuracy, as evidenced by its higher area under the curve (AUC) values. This indicates a more reliable performance in predicting LNM in PTMC, underscoring the potential of our nomogram to refine risk stratification and guide the management of patients with PTMC.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The discriminative power, calibration, and clinical utility of our nomogram in predicting LNM in PTMC were found to be high in both the training and validation sets. Additionally, when compared to other predictive models and nomograms, such as the BRAF V600E mutation model, 14 the sonographic features scoring system, and Liu's nomogram, 19 our tool demonstrated superior accuracy, as evidenced by its higher area under the curve (AUC) values. This indicates a more reliable performance in predicting LNM in PTMC, underscoring the potential of our nomogram to refine risk stratification and guide the management of patients with PTMC.…”
Section: Discussionmentioning
confidence: 91%
“…12,13 In contrast, a nomogram stands out as a graphical tool designed to fuse multiple variables, offering tailored estimates of the likelihood of specific outcomes, thereby addressing some of the limitations inherent in other approaches. 14 In this research, we aimed to devise and validate a model for the preoperative prediction of LNM in patients with PTMC, incorporating readily available preoperative information including both clinical and ultrasonographic features. 15 We hypothesize that our model will demonstrate robust performance and clinical utility in preoperatively predicting LNM in patients with PTMC and therefore impact on treatment options available for patients with PTMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that CRC cells could use the increased aberrant N-glycans to escape immune surveillance. Besides CRC, high-mannose N-glycan levels also elevated in papillary thyroid microcarcinoma ( 27 ), prostate cancer ( 28 ) and breast cancer ( 13 , 25 ), and they were frequently increased in cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%